2012
DOI: 10.1016/j.aquaculture.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Negative genetic correlations between production traits and head or bony tissues in large all-female rainbow trout (Oncorhynchus mykiss)

Abstract: Genetic parameters of production traits (growth, carcass yield, fillet yield) and bony tissues (head and vertebral axis) were estimated for large all-female rainbow trout Oncorhynchus mykiss reared in freshwater. Genetic parameters were estimated using REML at 16 months of age (1636 g) on 1962 DNA-assigned progenies from a partial factorial mating design with 60 dams and 100 sex-reversed sires. Highlights► Genetic parameters of production traits in rainbow trout ► Negative correlation between production traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
39
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 40 publications
13
39
2
Order By: Relevance
“…The heritability estimates for body weight measures (BW10 and BW13) and FW were in the range of 0.19–0.50 (Elvingson and Johansson, 1993; Neira et al, 2004; Kause et al, 2007) and 0.22–0.52 (Kause et al, 2002, 2007; Powell et al, 2008; Haffray et al, 2012), respectively, as previously reported for salmonids. Similarly, the heritability estimate for FY was in the interval previously reported for salmonids (0.03–0.38), and CV was in the upper range of estimates (0.12–6.5%) (Neira et al, 2004; Kause et al, 2007; Powell et al, 2008; Haffray et al, 2012). The heritability estimate for CAR ( h 2 = 0.62) was higher than previous estimates of 0.36–0.53 reported in the literature (Powell et al, 2008; Haffray et al, 2012).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The heritability estimates for body weight measures (BW10 and BW13) and FW were in the range of 0.19–0.50 (Elvingson and Johansson, 1993; Neira et al, 2004; Kause et al, 2007) and 0.22–0.52 (Kause et al, 2002, 2007; Powell et al, 2008; Haffray et al, 2012), respectively, as previously reported for salmonids. Similarly, the heritability estimate for FY was in the interval previously reported for salmonids (0.03–0.38), and CV was in the upper range of estimates (0.12–6.5%) (Neira et al, 2004; Kause et al, 2007; Powell et al, 2008; Haffray et al, 2012). The heritability estimate for CAR ( h 2 = 0.62) was higher than previous estimates of 0.36–0.53 reported in the literature (Powell et al, 2008; Haffray et al, 2012).…”
Section: Resultssupporting
confidence: 80%
“…Similarly, the heritability estimate for FY was in the interval previously reported for salmonids (0.03–0.38), and CV was in the upper range of estimates (0.12–6.5%) (Neira et al, 2004; Kause et al, 2007; Powell et al, 2008; Haffray et al, 2012). The heritability estimate for CAR ( h 2 = 0.62) was higher than previous estimates of 0.36–0.53 reported in the literature (Powell et al, 2008; Haffray et al, 2012). …”
Section: Resultssupporting
confidence: 69%
“…Despite these cumulated drawbacks, it has recently been shown by simulation based on real data that genetic gains in the range 0.30% to 0.95% units per generation should be achievable when selecting for improved fillet yield with 20% selection pressure in fish (Fraslin et al, 2018). Fillet yield may be used as a trait for selection, but residual fillet weight (rFW), which is fillet weight minus the expected fillet weight based on the linear regression of fillet weight on body weight, was proposed as a better alternative (Haffray et al, 2012a). This is because the heritability of ratio traits (here fillet yield = fillet weight/body weight) does not permit a reliable prediction of genetic change (Gunsett, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Selective breeding has been effective to increase the intervals between two consecutive baths/ treatments which lead to overall reduction in number of baths/treatments and ultimately reduction in the expenses incurred on AGD 16 . However, addition of AGD resistance in breeding goal traits will reduce selection response for other traits, particularly when AGD show unfavourable genetic correlations to any other traits 18,19 . The use of marker assisted selection (MAS) and/or genomic selection (GS) using molecular markers that are directly or indirectly linked to variation in causal loci could provide potent tools to overcome these challenges which may increase both selection accuracy as well as selection intensity as this allow also for within family selection 20,21 .…”
mentioning
confidence: 99%